2012
DOI: 10.1371/journal.pone.0032945
|View full text |Cite
|
Sign up to set email alerts
|

Rhodococcus Bacteremia in Cancer Patients Is Mostly Catheter Related and Associated with Biofilm Formation

Abstract: Rhodococcus is an emerging cause of opportunistic infection in immunocompromised patients, most commonly causing cavitary pneumonia. It has rarely been reported as a cause of isolated bacteremia. However, the relationship between bacteremia and central venous catheter is unknown. Between 2002 and 2010, the characteristics and outcomes of seventeen cancer patients with Rhodococcus bacteremia and indwelling central venous catheters were evaluated. Rhodococcus bacteremias were for the most part (94%) central line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…To the best of our knowledge, there are three studies regarding R. equi biofilm formation that together evaluated only ten isolates, six clinical (associated to chronic infection in humans) (Akhrass et al 2012, Remuzgo-Martínez et al 2013) and four from soil (Mart`yanov et al 2014). Akhrass et al (2012) found three strains positive for biofilm formation, while Remuzgo-Martínez et al (2013) verified only one.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, there are three studies regarding R. equi biofilm formation that together evaluated only ten isolates, six clinical (associated to chronic infection in humans) (Akhrass et al 2012, Remuzgo-Martínez et al 2013) and four from soil (Mart`yanov et al 2014). Akhrass et al (2012) found three strains positive for biofilm formation, while Remuzgo-Martínez et al (2013) verified only one.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, R. equi in established biofilms were recovered even after exposure to high ATM concentrations, however, CFU amount reduction was statically significant (Table 3). Two studies concerning antimicrobial susceptibility of clinical and environmental R. equi producing biofilm were performed by Akhrass et al (2012) and Mart`yanov et al (2014). The first study found R. equi biofilm reduced completely or partially by antimicrobial solutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biofilms are multicellular structures which are relevant clinically because of their extreme resistance to antibiotic therapy and are thus difficult to treat, even if the identical sessile cells are antibiotic susceptible (38). Significantly, biofilm formation by R. equi was recently reported, where biofilms formed on catheters were found to be the source of Rhodococcus bacteremia in cancer patients (2). Studies are under way in our laboratory to investigate the possible relationship between conjugation and biofilm formation in R. equi.…”
Section: Discussionmentioning
confidence: 99%
“…Methylene blue (0.05-0.15%) has been used for ALT in combination with 0.15% methyl paraben, 0.015% propyl paraben, and TSC 70 mg/mL or heparin sodium 10 units/mL, with no incompatibilities noted. 10,[98][99][100][101] The use of methylene blue in ALT has not become widespread due to a relative lack of supportive data and logistical issues.…”
Section: Miscellaneous Antiinfectivesmentioning
confidence: 99%